Optogenetic Control of Molecular Motors and Organelle Distributions in Cells. Issue 5 (21st May 2015) - Duan, Liting; Che, Daphne; Zhang, Kai; Ong, Qunxiang; Guo, Shunling; Cui, Bianxiao
Summary: Intracellular transport and distribution of organelles play important roles in diverse cellular functions, including cell polarization, intracellular signaling, cell survival, and apoptosis. Here, we report an optogenetic strategy to control the transport and distribution of organelles by light. This is achieved by optically recruiting molecular motors onto organelles through the heterodimerization of Arabidopsis thaliana cryptochrome 2 (CRY2) and its interacting partner CIB1. CRY2 and CIB1 dimerize within subseconds upon exposure to blue light, which requires no exogenous ligands and low intensity of light. We demonstrate that mitochondria, peroxisomes, and lysosomes can be driven toward the cell periphery upon light-induced recruitment of kinesin, or toward the cell nucleus upon recruitment of dynein. Light-induced motor recruitment and organelle movements are repeatable, reversible, and can be achieved at subcellular regions. This light-controlled organelle redistribution provides a new strategy for studying the causal roles of organelle transport and distribution in cellular functions in living cells. Graphical Abstract: Highlights: We developed an optogenetic tool to control organelle distributions in cells Motor proteins can be recruited to organelle membrane by dimerization of CRY2-CIB1 Organelles can be driven toward cell nucleus or toward cell periphery by light Light-induced organelle transport can be spatially controlled at subcellular region Abstract : Based on the heterodimerization of cryptochrome 2 and CIB1, Duan et al. develop an optogenetic tool to control organelle distribution in cells by light-inducible recruitment of molecular motors to organelle outer membrane.